PROBLEMS AND SOLUTIONS OF INTEGRATING FOUR SKILLS (LISTENING, READING, SPEAKING, WRITING) IN ESP CLASSES - Qodirjonova Xursanoy Ravshanbek qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article examines the key problems and practical solutions related to the integration of four language skills — listening, reading, speaking, and writing — in English for Specific Purposes (ESP) classrooms. Unlike General English, ESP requires learners to master discipline-specific communication competencies, making skill integration particularly challenging yet essential. The study identifies major obstacles such as lack of authentic materials, time constraints, teacher training gaps, and low learner motivation. Based on analysis of ESP teaching models and classroom case studies, the article proposes effective solutions including task-based learning, content-based instruction, technology integration, and skill-loop lesson design. The findings suggest that integrated skill instruction in ESP not only improves language proficiency but also enhances professional readiness.